Improving Voluntary Compliance Using Power of Tax Administrators: The Mediating Role of Trust - Abdul Rashid, Siti Fatimah; Ramli, Rosiati; Palil, Mohd Rizal; Mohd Amir, Amizawati (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study examines the mediating role of reasonbased trust and implicit trust in the relationship between different social powers (namely coercive, reward, legitimate foundation and persuasive power) and voluntary tax compliance motivations (namely voluntary and committed cooperation). Design/Methodology/Approach: A quantitative research design using survey questionnaires was applied to 388 professional taxpayers. Structural equation modelling (SEM) using AMOS Graphics was employed to analyse the data. Research findings: The findings on the mediating role of trust in the relationship between coercive and persuasive power with intended voluntary tax compliance align with the extension of the Slippery Slope Framework (eSSF). The reason-based trust was found to mediate the relationship between coercive power and committed cooperation partially. The analysis also indicates that implicit trust partially mediates the relationship between persuasive power and voluntary cooperation. Furthermore, the analysis confirms that both reason-based and implicit trust partially mediate the relationship between reward power with voluntary cooperation and committed cooperation. About legitimate foundation power, only implicit trust seems to mediate the relationship with committed cooperation partially. However, the analysis shows inconsistent mediation for this relationship. Theoretical contribution/Originality: This study highlights the importance of tax administrators’ power, especially reward and persuasive power, as means to instil trust in tax administrators to improve voluntary tax compliance. Practitioner/Policy implication: This study offers interesting insights to tax administrators, specifically the Inland Revenue Board Malaysia (IRBM), to improve voluntary tax compliance by using the power of IRBM with aims to foster trust in IRBM. Research limitation/Implications: The limitation of this study is that it studies voluntary tax compliance as voluntary cooperation and committed cooperation, representing taxpayers’ intention to comply. Therefore, future studies should consider extending this study by assessing the relationships to include actual behaviour. Keywords: Coercive Power, Implicit Trust, Power, Reason-based Trust, Reward Power, Slippery Slope Framework, Tax Compliance, Trust JEL Classification: H21